Sistema de información web para mejorar la gestión académica de la I.E.P. Jan Komensky de la Ciudad de Trujillo - Ortiz Briceño, Rogger Alejandro (2020)
This thesis entitled "WEB INFORMATION SYSTEM TO IMPROVE THE ACADEMIC MANAGEMENT OF THE I.E.P. JAN KOMENSKY OF THE CITY OF TRUJILLO" has been elaborated around the problematic reality present in the aforementioned institution which aims to demonstrate that the application of a computer system can improve its academic management and consequently achieve a fast and efficient reach of its objectives. I.E.P. Jan Komensky is a company dedicated to providing education service for the levels: initial, primary and secondary in the city of Trujillo. Before carrying out this study the company performed most of its academic activities manually, the information was obtained slow and generally very arduous and took a long time for its implementation bringing a high degree of dissatisfaction to the responsible staff. After carrying out the corresponding analysis, the development and implementation of a web information system for the treatment and automation of the academic management of the company was determined. The decision to choose the use of web technologies was due to the advantages that they present mainly due to their availability at any time and their use from any device with an internet connection. For the development of the information system, modern technologies and tools were used, the PHP programming language supported by the Laravel framework was used, responsive adoption techniques were used to different devices through CSS supported in the framework Bootstrap. MySQL was used as database manager and the management of the system development project was carried out using the RUP methodology. After the implementation of the computer system in the company it was possible to dissolve the problematic cause of the present study, noticing now efficient way to enroll students (that was reduced from 58.28 min to 7.93 min), the rapid generation of student report cards (that was reduced from 44.28 min to 3.05 min) and a considerable increase in the satisfaction of the company's staff (from 33% increased to 91.38%) and the parents of the students (from 33.89% increased to 90.89%), so we can conclude that currently the academic management of the I.E.P. Jan Komensky has improved, fulfilling in this way the objectives set out in this project.